Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/nu13082795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet and Dietary Components on the Composition of the Gut Microbiota

Abstract: Diet and dietary components have profound effects on the composition of the gut microbiota and are among the most important contributors to the alteration in bacterial flora. This review examines the effects the “Western”, “plant-based”, “high-fat”, “medical ketogenic”, and “Mediterranean” diets have on the composition of the gut microbiota in both mice and human subjects. We show that specific dietary components that are commonly found in the “plant-based” and “Mediterranean” diet play a role in shifting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
165
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(235 citation statements)
references
References 93 publications
(219 reference statements)
3
165
0
5
Order By: Relevance
“…Moreover, although we did not identify any relationship between nutrient intake and the measured skin parameters, that influence is expected to exist due to the impact of food in the gut, particularly fiber and water intake [2,44].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Moreover, although we did not identify any relationship between nutrient intake and the measured skin parameters, that influence is expected to exist due to the impact of food in the gut, particularly fiber and water intake [2,44].…”
Section: Discussionmentioning
confidence: 66%
“…New insights in the field of nutrition increasingly support the evidence of a close relationship between diet and health, namely skin health [2,71]. Diet is a major regulator of the intestinal microbiota, and short-term changes in the diet have the ability to rapidly alter gut bacteria [44,72].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gut microbiota dysbiosis may lead to increased permeability of the intestinal mucosal barrier, infection, and excessive inflammatory response, as well as an imbalance of T cell subsets, which has been described in asthma ( 26 ), rheumatoid arthritis ( 27 ), inflammatory bowel disease ( 28 ), multiple sclerosis ( 29 ), and MG ( 30 ), among others. Accordingly, regulating the immune imbalance of Thl7/Treg cells and inducing the reconstruction of immune tolerance may become a potential treatment modality for autoimmune diseases, such as MG. Studies have revealed that environmental factors, especially dietary factors, can alter the gut microbiota composition and its metabolic activity , which produce adverse implications for human health ( 31 ). For instance, alterations in the gut microbiota caused by a Western high-fat diet have recently been recognized as a major contributing factor to the colorectal cancer epidemic ( 32 ) .…”
Section: Introductionmentioning
confidence: 99%